El nuevo potro indomable: El problemático estándar de motivación de los laudos exigido por las cortes peruanas - Cantuarias Salaverry, Fernando (2015)
The author makes a critical analysis of the current situation of the Arbitration in Peru, from various court decisions that have identified the standard of motivation that must have an arbitration award. In this way, the author indicates that the consequences of annulling arbitral awards by improper motivation, insufficient motivation or follow criteria of the Arbitral Tribunal are severe and it affects all the progress that has been obtained in the arbitration in these last two decades.